2016
DOI: 10.1098/rsos.160463
|View full text |Cite
|
Sign up to set email alerts
|

Sex roles, parental care and offspring growth in two contrasting coucal species

Abstract: The decision to provide parental care is often associated with trade-offs, because resources allocated to parental care typically cannot be invested in self-maintenance or mating. In most animals, females provide more parental care than males, but the reason for this pattern is still debated in evolutionary ecology. To better understand sex differences in parental care and its consequences, we need to study closely related species where the sexes differ in offspring care. We investigated parental care in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 51 publications
(130 reference statements)
1
42
0
Order By: Relevance
“…However, when feeding dependent offspring, individual male black coucals have a four-fold higher feeding rate than individual white-browed coucals and, in between feeding bouts, rest only 1/3rd of the time white-browed coucals do (Goymann et al, 2016). These data suggest a substantial difference in time and energy costs of offspring care between male black coucals and pairs of whitebrowed coucals.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…However, when feeding dependent offspring, individual male black coucals have a four-fold higher feeding rate than individual white-browed coucals and, in between feeding bouts, rest only 1/3rd of the time white-browed coucals do (Goymann et al, 2016). These data suggest a substantial difference in time and energy costs of offspring care between male black coucals and pairs of whitebrowed coucals.…”
Section: Introductionmentioning
confidence: 66%
“…Further details regarding the study site can be found in the work by Goymann et al (2015Goymann et al ( , 2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is a nesting Old World Cuckoo, occurring in sub-Saharan Africa (Fry et al 1988). The breeding system and life history of White-browed Coucals have only recently been studied (Goymann et al 2015(Goymann et al , 2016. They are year-round resident birds that live in socially monogamous pairs, and both partners contribute to parental care.…”
Section: Introductionmentioning
confidence: 99%